Nanomaterials for urban farming - Putra, Ann Edmonda Tommy (Nanyang Technological University, 2021)
Nanotechnology plays a critical part in fertilizer to increase crop productivity and quality in agricultural products. Carbon dots are widely researched as a promising alternative to costly and harmful conventional NPK (Nitrogen-Phosphorous-Potassium) chemical fertilizers [6]. Carbon dots (CD) can improve nutrient delivery efficiency, sustainable and combined with antibacterial properties to increase crop yield with low land availability in the shortest time. In this experiment, CD derived from Citric Acid was synthesized by the hydrothermal process (200°C, 10 h) as it widely available, inexpensive and safe for the environment. It has been widely researched for increasing plant growth and quality by improving photosynthesis [8]. CD derived Copper Chloride (CuCD) was also utilized and synthesized with Citric Acid by the hydrothermal process (200°C, 10 h). From past research, the presence of Copper nanoparticles has a good anti-bacterial property from increasing antioxidants levels [9,10,35]. We intended to examine further about the physiological response, phytotoxicity and water uptake by cultivating mung beans with CD, CuCD from 0.3 gr copper chloride, and CuCD from 0.5 gr copper chloride with concentration ranging from 0.1 mg/ml to 1 mg/ml. Characterization of functional groups of CD and CuCD were identified using FTIR while Excitation and Emission spectrum of CuCD were evaluated using UV-Vis Spectrometer UV-2700 and RF-6000 Spectrofuorophotometer. The result of this study indicated that there is an induced physiological response from the height of the stems and roots and an increase in water uptake. This result could be a promising alternative fertilizer for urban farming application.